Thermal Performance of a Double-Action Pulsed Jet CPU Cooler - Chandratilleke, Tilak; Rakshit, Dibakar (IEEE, 2013)
More efficient and compact thermal management techniques are critical for the development of Central Processing Units (CPU) embedded in complex and powerful modern computer systems. Introducing a technological alternative to conventional fan-cooled systems, this paper presents an experimental investigation of a double-action CPU cooler based on the pulsed (or synthetic) jet principle.The study develops a prototype of this new CPU cooler and tests it for a range of operating conditions to ascertain its cooling capabilities. The performance of this device is compared with a conventional fan CPU heat sink design for evaluating the relative thermal advantages of the new configuration. It is observed that the pulsed-jet CPU cooler achieves about 1.5 times more heat removal rate than a comparable fan CPU cooler. Whilst thermal optimisation is feasible, it is recognised that this pulsed jet arrangement has unique surface cooling ability without additional fluid circuits, making it particularly desirable for high-capacity electronic cooling applications.